2014
DOI: 10.1590/s1415-43662014000200008
|View full text |Cite
|
Sign up to set email alerts
|

Estimativa da produtividade de trigo em função da adubação nitrogenada utilizando modelagem neuro fuzzy

Abstract: R E S U M OAtualmente, novas técnicas de processamento de dados, tais como redes neurais, lógica nebulosa (fuzzy) e sistemas híbridos, são utilizadas para elaborar modelos de predição em sistemas complexos e estimar parâmetros desejados. Neste artigo investigou-se a habilidade de se desenvolver um modelo de inferência adaptativo neuro fuzzy para estimação da produtividade de trigo utilizando-se uma base de dados da combinação dos seguintes tratamentos: cinco doses de N (0, 50, 100, 150 e 200 kg ha -1 ); três f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
(15 reference statements)
1
11
0
5
Order By: Relevance
“…The use of artificial neural networks has presented itself as an efficient alternative to conventional models in the recognition of patterns and simulation of cultivation processes (Silva et al, 2014;Soares et al, 2014). Rogenski et al (2012) found efficiency of the artificial neural networks in the estimation of infection percentage of leaf diseases in wheat, as assistance in decision-making.…”
Section: Resultsmentioning
confidence: 99%
“…The use of artificial neural networks has presented itself as an efficient alternative to conventional models in the recognition of patterns and simulation of cultivation processes (Silva et al, 2014;Soares et al, 2014). Rogenski et al (2012) found efficiency of the artificial neural networks in the estimation of infection percentage of leaf diseases in wheat, as assistance in decision-making.…”
Section: Resultsmentioning
confidence: 99%
“…[4], contudo necessita de regras para produzir os resultados almejados. As regras devem ser elaboradas por especialistas que fornecem sua experiência profissional para a elaboração de um sistema de inferência [14]. Dessa forma a lógica fuzzy representa uma proposta importante e pode trazer grandes subsídiosà agricultura com a interpretação de dados linguísticos através de programas computacionais [11].…”
Section: Resultsunclassified
“…Besides, combined simulation models allow us to analyze different scenarios, considering several factors that influence the productivity of each crop [41]. Thus, the integration of two or more models aims to obtain a more efficient model for the prediction of agricultural crops [42]. Reference [43] combined the expolinear-logistic model and the Gompertz model to estimate the variation of shoot dry matter accumulation in sugarcane cultivars.…”
Section: Resultsmentioning
confidence: 99%
“…Reference [43] combined the expolinear-logistic model and the Gompertz model to estimate the variation of shoot dry matter accumulation in sugarcane cultivars. Reference [42] combined models of Fuzzy Logic and Neural Networks to estimate wheat productivity as a function of nitrogen fertilization. Reference [41] using the combination of mathematical models were able to predict satisfactorily the grain productivity of the soybean crop, evidencing the best irrigation strategies that result in high grain productivity.…”
Section: Resultsmentioning
confidence: 99%